2010
DOI: 10.1007/bf03326154
|View full text |Cite
|
Sign up to set email alerts
|

Spatial inequality in municipal solid waste disposal across regions in developing countries

Abstract: ABSTRACT:The regional inequalities in socio-economical characteristics such as income, population density, age composition, unemployment rate and the education level may bring about variation in waste generation, recycling and collection. Using environmental Kuznets curve, the factors affecting municipal solid waste disposal are examined. The results demonstrate that an inverted N-shaped curve executes on municipal solid waste disposal for all regions. As personal disposable income increases, per capita munici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 42 publications
1
28
0
2
Order By: Relevance
“…Since then, there have been changes in the behaviors and attitudes of people toward environmental issues. However, while a majority of people have adopted environmental attitudes, environmentally responsible behaviors have not been reflected in life in the same level (Tarant and Cordel, 1977;Nouri et al,2008;Chen, 2010;Chen et al,2010). In the 1980s, a different viewpoint was brought up by scientists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, there have been changes in the behaviors and attitudes of people toward environmental issues. However, while a majority of people have adopted environmental attitudes, environmentally responsible behaviors have not been reflected in life in the same level (Tarant and Cordel, 1977;Nouri et al,2008;Chen, 2010;Chen et al,2010). In the 1980s, a different viewpoint was brought up by scientists.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Robertson and Burdge (1998) stated that the people living in the urban areas are more concerned with environmental issues than those living in the rural areas. Tehrani et al 2009 and2010;Thapa (1999) observed some changes in the environmental attitudes and behaviors of the students due to their education. He found out that the students who had education on environment were more aware of environmental attitudes than the other students.…”
Section: Introductionmentioning
confidence: 99%
“…Its production increased from 1,480 GWH in 2000 to 3,091.9 GWH in 2011, and its installed capacity reached 624.4 MW by end of 2011 with share of 18.5 %. Due to the awareness of environmental consciousness, municipal solid waste (MSW) generation has decreased, and its consequence leads to a continual reduction in the expansion of MSW incineration facilities (Chen and Chen 2008;Chen 2010). Thus, the installed capacity of WTE plants has remained constant since 2007.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, in terms of low population served by sanitation services and poor infrastructure, the waste generated and uncollected is disposed in open dumps polluting the local environment. In developing countries, all the explanatory variables including economic factors, social characteristics and geographical barriers are found to influence municipal solid waste disposal significantly (Chen, 2010). Also, new EU members have a low share of access of rural population to sanitation services leading to illegal dumping.…”
Section: Geography Of Waste And/or Waste Management Related To Geogramentioning
confidence: 99%